The impact of artificial intelligence on logic skills, critical thinking, and student creativity - Suryanto, Agnes Febriyanti; Wajdi, Majid; Sahoo, Prakash Kumar; Wu, QingHao; Yusof, Norhayati Mohd; Chan, Yuen Fook (Journal of Language, Literature, Social and Cultural Studies, 2025)
The primary objective of this study centred on examining the influence of artificial intelligence (AI) on students’ cognitive development and creative capabilities within higher education. More specifically, the research sought to analyse the relationship between AI usage and the development of key cognitive faculties, such as analytical intelligence, logical reasoning, and creative problem-solving among university students. In undertaking this investigation, the researchers adopted a qualitative methodology, engaging primarily with secondary data sources. By systematically reviewing existing literature—from peer-reviewed scientific journals, scholarly articles, and other reputable academic publications—they were able to construct a comprehensive synthesis of current insights into how students are integrating AI tools into their academic routines and how these tools are perceived in the university setting. The findings of the analysis indicate that AI technologies have a significant, and in many cases positive, impact on students’ data analysis abilities and their comprehension of complex academic content. A noteworthy proportion of students reported that AI-based tools enabled them to deconstruct challenging subject matter more efficiently. This utility appeared to translate into noticeable improvements in their analytical intelligence. Furthermore, AI was highlighted as advantageous for synthesizing disparate pieces of information, thereby equipping students to approach and solve intricate academic problems more effectively. Nevertheless, while these technological benefits are substantial, the study drew attention to an important caveat: the tendency toward over-reliance on AI-driven solutions. For a subset of students, the ease and convenience offered by AI led to a diminished practice of independent problem-solving. In their reliance on automated assistance, some students risked neglecting the active engagement necessary for developing robust critical thinking skills and independent intellectual growth. This over-dependence on technological aids may, in the long term, hinder the cultivation of original thoughts and creative approaches essential at the tertiary level of education.